Perancangan Bisnis Buku Komik Sejarah Manga - Deborah, Tulus; Saniscara, Pramesti (Jurnal VICIDI, 2020)
This Japanese / manga comic book history book gives reference to image style techniques, and introduces the early Japanese comics. The purpose of this research is to find out how to design the content of Japanese history books that interest people to read. The research was done by using mix method, this research has two ways, namely data retrieval in primary and secondary. Primary collection consists of qualitative and quantitative data collection. While taking secondary data using literature book.